Analisis Manajemen Fasilitas Conveyor Belt untuk Meningkatkan Efisiensi Alur Bagasi di Terminal Kedatangan Juwata Tarakan - Simbolon, Rayhan Grasias Moliendo; Ubaedillah, Ubaedillah; Praptiningsih, Nunuk (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
This study aims to analyze the facility management of conveyor belts and identify the obstacles affecting baggage flow efficiency at the Arrival Terminal of Juwata Tarakan Airport. A descriptive qualitative method was employed through field observation, interviews with key airport units (TIS, ME, and Ground Handling), and documentation from logbooks and visual records. The findings indicate that issues such as malfunctioning sensors, misaligned conveyor joints, and the absence of protective padding lead to inefficiencies in baggage flow. These problems are closely related to the lack of implementation of key facility management principles, such as preventive maintenance, standard inspections, and inter-unit coordination. This research highlights the importance of managerial improvements, including the development of SOPs, regular evaluations, and adherence to ICAO standards and PM 36 of 2021 regulations. Strategic recommendations are proposed to enhance baggage system performance and service quality.